1995
DOI: 10.1016/s0022-5347(01)66942-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Resistive Index Following Extracorporeal Shock Wave Lithotripsy

Abstract: Elderly patients have a higher risk of post-ESWL renal tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 21 publications
3
27
1
1
Order By: Relevance
“…Currently, an increase in RI values is expected after SWL therapy, which has been confirmed in many studies, though there are a few exceptions [11,18]. In the present study, we found higher RI values after SWL sessions in patients in both groups, comparable to that reported previously in literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Currently, an increase in RI values is expected after SWL therapy, which has been confirmed in many studies, though there are a few exceptions [11,18]. In the present study, we found higher RI values after SWL sessions in patients in both groups, comparable to that reported previously in literature.…”
Section: Discussionsupporting
confidence: 91%
“…Measurement of the renal arterial resistive index (RI) of the kidney is a recently applied successful radiological tool that can reveal the resistance of intrarenal arteries, indirectly demonstrating effective renal blood flow [8][9][10]. Recently, it was shown that shock waves may decrease renal blood flow, which can lead to transient impairments in renal function after SWL [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, one prospective study showed age as a significant risk factor, with an increase in intrarenal resistive index in patients 60 years of age and older 62 . Other studies as well have reported an increase in hypertension among older lithotripsy patients 66 . It appears that transient hypertension can result from formation of subcapsular hematomas 52 .…”
Section: The Potential For Long-term Adverse Effects Due To Swl: Hypementioning
confidence: 87%
“…A number of clinical studies have suggested that new-onset hypertension is a potential longterm consequence of SWL 1,[62][63][64][65][66][67] . Among these, one prospective study showed age as a significant risk factor, with an increase in intrarenal resistive index in patients 60 years of age and older 62 .…”
Section: The Potential For Long-term Adverse Effects Due To Swl: Hypementioning
confidence: 99%
“…They indicated that the relationship was linear. 26 It can be justified as follows: (a) applying different lithoclast sets in these three studies, (b) the difference found between these three studies considering treatment method, number, and power of shocks, and (c) different measurement times of vascular RI in these studies. Nazaroglu et al demonstrated that there was no meaningful relationship between the applied energy and increase of vascular RI.…”
Section: Discussionmentioning
confidence: 99%